Aqueous Pretreatment of Plant Biomass for Biological and Chemical Conversion to Fuels and Chemicals 2013
DOI: 10.1002/9780470975831.ch14
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Features of Pretreated Biomass that Influence Macro‐/Micro‐Accessibility and Biological Processing

Abstract: Lignocellulosic biomass containing about 55-65 wt% sugars in the form of polymeric structural carbohydrates can be a sustainable feedstock for production of a variety of sugars that can in turn be converted into fuels and chemicals [1][2][3]. For biological deconstruction of structural carbohydrates to sugars, tiny protein molecules called enzymes need to reach appropriate substrates to depolymerize them. In native plants however, carbohydrates are trapped in a complex matrix comprising non-sugar constituents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 296 publications
(418 reference statements)
1
52
0
2
Order By: Relevance
“…One of the structural properties of the model samples, the "accessibility to cellulase," can be also deduced from the cellulase adsorption rate [13,14]. In particular, it is described as initial accessibility, because the accessibility is altered by the cellulase action known as amorphogenesis [15].…”
Section: Resultsmentioning
confidence: 99%
“…One of the structural properties of the model samples, the "accessibility to cellulase," can be also deduced from the cellulase adsorption rate [13,14]. In particular, it is described as initial accessibility, because the accessibility is altered by the cellulase action known as amorphogenesis [15].…”
Section: Resultsmentioning
confidence: 99%
“…The differential increases may reflect the difference in accessibility between cellulose and hemicellulose, or the heterogeneity of cellulose fiber morphology. Given that several structural features such as fibril length and pore size distribution determine cellulose accessibility, the results indicate that they may influence cellulase binding and hydrolytic efficacy even at smaller particle diameters.…”
Section: Resultsmentioning
confidence: 94%
“…In recent times, the accessibility has been posited to consist of two components, “macroaccessibility” and “microaccessibility.” Macroaccessibility denotes the accessibility of the enzyme to the cellulose surface, and is reduced by the presence of hemicellulose and lignin, which bind the surface. Pretreatment‐based delignification is predominantly held to increase macro‐accessibility, bringing no further improvements beyond specific limits . Once access to the cellulose surface reaches critical mass however, the enzyme must bind productively to the reducing ends of cellulose fibrils, to generate soluble oligomers .…”
Section: Resultsmentioning
confidence: 99%
“…This cellulose may appear as part of the amorphous population when measured by many of the crystallinity index measurement methods. Several studies have indicated that cellulolytic components not only catalyze cellulose hydrolysis but can significantly disrupt cellulose structure at the same time . Pu et al used the NMR methodology developed by Larsson and Westlund to probe cellulose crystallinity and defined a para ‐crystalline population that is less ordered than crystalline cellulose but more ordered than truly amorphous cellulose.…”
Section: Resultsmentioning
confidence: 99%